In-season training periodization of professional soccer players - Los Arcos, A.; Mendez-Villanueva, A.; Martinez-Santos, R. (Biology of Sport, 2017)
The aim of this study was to quantify the seasonal perceived respiratory and muscular training loads (i.e., sRPEres-TL and sRPEmus-TL) completed by elite-oriented young professional soccer players. Twentyfour players (20.3 ± 2.0 years) belonging to the same reserve team of a Spanish La Liga club participated in this study. Only the players that were available to train for a whole week with the team and also to play the weekly game were considered: Starters, players that participated in the match for at least 45 min and Non- Starters, players that did not participate or played less than 45 minutes in the match. The competitive period was analysed after the division into 5x6-8 week blocks and 35x1 week microcycles. Data were also analysed with respect to number of days before the immediate match. Weekly TL variation across the in-season blocks was trivial-small for both groups except between Block 2 and Block 3 (ES= moderate). Substantial TL differences (ES= small-very likely) were found between training days, the TL pattern being a progressive increase up to MD-3 followed by a decrease until MD-1. Except for the match, sRPEres-/sRPEmus-TL was very similar between Starters and Non-Starters. In summary, perceived TL across the season displayed limited variation. Coaches periodized training contents to attain the highest weekly TL 72 hours before the match to progressively unload the players between MD-3 and the match day. The data revealed that the TL arising from the weekly game was solely responsible for the observed higher weekly TL of Starters in comparison with Non-Starters.